Pemanfaatan Tepung Tulang Ayam Pada Pakan untuk Meningkatkan Produktifitas Telur Itik Mojosari di Dusun Singgihan, Kecamatan Munjungan, Kabupaten Trenggalek - Mifakhul Khasanah; Tuntas Bagyono; nart Narto (Poltekkes Kemenkes Yogyakarta, 2015)
Organic waste, particulary chicken bones, have not been well managed. Therefore, it is potential to give negative effect to the environment. One of proper bone waste processing is to utilizeit as additional ingredient for duck feed. The purpose of the study was to know the effect ofchicken bones powder addition at 3 %, 5 %, and 7 % concentration on the increase of egg productivity in terms of their weight and quantility. The research was an experiment with pre-testand post-test with only group design. The object of the study was 60 Mojosari Ducks aged ninemonth in Singgihan Village of Trenggalek Regency. The feeding was given in 15 days. The data obtained were analysed by using one way anava and Kruskal Walli tests, and subsequentlywith paired t-test, at 95 % confidence level. The result showed that the increasing of egg weightproduced by each treatment group were significantly different (p-value < 0,001) and the 7 %concentration gave the highest average, i.e. 5,1 gram. And so was for egg quantity parameter,the study results showed that each treatment group yielded different increase number of duckeggs (p-value < 0,001), where the highest average, i.e. 2,1 eggs, was obtained from the 7 %concentration. It can be concluded that chicken bones powder addition to duck feeds has gavepositive effect.